2017
DOI: 10.1016/j.celrep.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A Targetable EGFR-Dependent Tumor-Initiating Program in Breast Cancer

Abstract: Therapies targeting epidermal growth factor receptor (EGFR) have variable and unpredictable responses in breast cancer. Screening triple-negative breast cancer (TNBC) patient-derived xenografts (PDXs), we identify a subset responsive to EGFR inhibition by gefitinib, which displays heterogeneous expression of wild-type EGFR. Deep single-cell RNA sequencing of 3,500 cells from an exceptional responder identified subpopulations displaying distinct biological features, where elevated EGFR expression was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 26 publications
(33 reference statements)
1
55
0
Order By: Relevance
“…it is likely that synergistic combinations with other targeted agents are necessary to achieve efficacy that is sufficient for clinical success [43][44][45][46][47][48][49] . We therefore tested carfilzomib and afatinib in combination with each of the 176 selected drugs, at a 10-fold lower dose (1 µM) relative to prior screening assays, in four basal-like PDXs (HCI01, UCD52, WHIM2, WHIM30) (Supplementary File S2).…”
Section: Carfilzomib and Afatinib Have Supra-additive Trends When Commentioning
confidence: 99%
“…it is likely that synergistic combinations with other targeted agents are necessary to achieve efficacy that is sufficient for clinical success [43][44][45][46][47][48][49] . We therefore tested carfilzomib and afatinib in combination with each of the 176 selected drugs, at a 10-fold lower dose (1 µM) relative to prior screening assays, in four basal-like PDXs (HCI01, UCD52, WHIM2, WHIM30) (Supplementary File S2).…”
Section: Carfilzomib and Afatinib Have Supra-additive Trends When Commentioning
confidence: 99%
“…TNBC is biologically aggressive and has the poorest prognosis when compared to other subtypes 3 . Previous study reported that EGFR is a potential target for TNBC 7 . In this work, epigallocatechin and epicatechin metabolites had notable predicted binding affinity towards EGFR kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…But different from previous subtypes, triple negative breast cancer is not responded very well to hormone treatment and HER2 antibody, and often treated with systemic chemotherapy. Previous study found that epidermal growth factor receptor (EGFR) kinase inhibitor, gefitinib, was able to halt the TNBC cell outgrowth in vitro 7 . Thus ER, HER2, EGFR served as important targets in breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…To that end, particular effort should be taken to carefully characterize the cellular states of preclinical models and understand their relationship to cellular states observed in patients, as different models might recapitulate different tumor compartments, as recently shown in H3 K27M-mutant glioma (Filbin et al 2018). Future work applying similar strategies will interrogate the developmental lineages and putative CSC programs in a range of malignancies (Savage et al 2017). In addition, identification of putative CSCs by scRNA-seq should be followed by functional studies to test the tumor initiation capacity and drug resistance of these subpopulations.…”
Section: Developmental Lineages and Cancer Stem Cellsmentioning
confidence: 99%